1991
DOI: 10.1021/jf00002a022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a commercial soybean cultivar and an isoline lacking the Kunitz trypsin inhibitor: composition, nutritional value, and effects of heating

Abstract: The content and heat stability of protease inhibitors of a standard cultivar (Williams 82) and an isoline (L81-4590) lacking the Kunitz trypsin inhibitor (KTI) were measured by using enzyme inhibition and enzyme-linked immunosorbent assays (ELISA). The KTI content of the isoline was less than 0.2% compared to Williams 82, with the exact content depending on the extent of cross-pollination of the soybeans. Steam heating of the isoline flour (121 °C, 20 min) resulted in a near-zero level of trypsin inhibitory ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
2
12

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 29 publications
8
73
2
12
Order By: Relevance
“…Extrusion also leads to starch gelatinisation and reduces the activity of trypsin inhibitors, which improves the conditions for efficient digestion of proteins in the small intestine of pigs (O'Doherty and Keady, 2001) and chickens (Arija et al, 2006). Crude genetically enhanced soybeans (Soja Lana) was as expected had a much lower level of trypsin inhibitors in comparison with the standard raw soybeans, as Kunitz trypsin inhibitor antitrypsin, main component of the seed (Friedman et al, 1991). Soybean varieties with low levels of Kunitz inhibitors may have different levels of trypsin inhibitors, depending on the spot they are grown (Kumar et al, 2003), the presence of other types of trypsin inhibitors (Tan- Wilson et al, 1987), variations in the level lipoksigegenase (Machado et al, 2008) and anti-nutritive factors such as phytates and tannins (Liener, 1994).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Extrusion also leads to starch gelatinisation and reduces the activity of trypsin inhibitors, which improves the conditions for efficient digestion of proteins in the small intestine of pigs (O'Doherty and Keady, 2001) and chickens (Arija et al, 2006). Crude genetically enhanced soybeans (Soja Lana) was as expected had a much lower level of trypsin inhibitors in comparison with the standard raw soybeans, as Kunitz trypsin inhibitor antitrypsin, main component of the seed (Friedman et al, 1991). Soybean varieties with low levels of Kunitz inhibitors may have different levels of trypsin inhibitors, depending on the spot they are grown (Kumar et al, 2003), the presence of other types of trypsin inhibitors (Tan- Wilson et al, 1987), variations in the level lipoksigegenase (Machado et al, 2008) and anti-nutritive factors such as phytates and tannins (Liener, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…The growth depression could be explained by other heat-labile antinutritional factors present in raw soybeans -Bowman-Birk trypsin inhibitor and lectin. Previous results suggest that simple removal of Kunitz inhibitor without any intervention upon Bowman-Birk inhibitor, although allowing a reduction of processing costs (Friedman et al, 1991) does not appear to solve a problem of direct livestock nutrition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Han et al (1991) reported that raw Kunitz-inhibitor-free soybean (KFSB) has better nutritional value than conventional raw soybean but lower than commercial soybean meal in chicks. The raw KFSB has 16 times lower trypsin inhibitor content than commercial soybean meal, but the Birkman inhibitor contents were similar (Friedman et al, 1991). This means that KFBS requires the same heat treatment as commercial soybean meal.…”
Section: Acta Veterinaria Hungarica 52 2004mentioning
confidence: 93%